Pengaruh Risiko Kredit, Tingkat Kecukupan Modal, dan Ukuran Perusahaan Terhadap Return on Assets (ROA) Bank yang Terindeks INFOBANK15 - Wildan Army Abdillah; Muhammad Iqbal Nurfauzan (JURNAL BISNIS STRATEGI, 2022)
Profitability is the company's ability to seek profit, through the ability of resources and profitability to control the size of a company to determine its assets. This study aims to determine the effect of credit risk, capital adequacy level and firm size on profitability. The research method used is descriptive and verification methods. The subjects of this study were conventional banks registered with INFOBANK15 for the period 2009-2019 with a total sample of 14 banks and 153 observational data. Statistical analysis used in this study is panel data regression. The results of the study stated that credit risk and capital adequacy level had no effect on profitability, while firm size had a significant effect on profitability.